Medical Gas Therapy for Tissue, Organ, and CNS Protection: A Systematic Review of Effects, Mechanisms, and Challenges (Adv. Sci. 13/2022). Issue 13 (5th May 2022) - Zafonte, Ross D.; Wang, Lei; Arbelaez, Christian A.; Dennison, Rachel; Teng, Yang D.
Abstract : Medical Gas Therapy The frontispiece exhibits an artistic view of the history (≈1550s BC–2020s AD) for medical gas therapy development. In article number 2104136 by Ross D. Zafonte, Yang D. Teng, and co‐workers, the cytoprotection mechanisms, data qualities, and challenges of gas agents are systematically reviewed. Whereas gas molecules protected cells in safe dosages, validating their therapeutic targets remained an urgent demand. Review and image design: Y.D. Teng. Image artwork: R. Dennison and Y.D. Teng.